Systematic review of global clinical practice guidelines for neonatal hyperbilirubinemia. Issue 1 (19th January 2021) - Zhang, Meng; Tang, Jun; He, Yang; Li, Wenxing; Chen, Zhong; Xiong, Tao; Qu, Yi; Li, Youping; Mu, Dezhi
Abstract : Objective: Hyperbilirubinemia is one of the most common clinical symptoms in newborns. To improve patient outcomes, evidence-based and implementable guidelines are required. However, clinical guidelines may vary in quality, criteria and recommendations among regions and countries. In this study, we aimed to systematically assess the quality of guidelines using the Appraisal of Guidelines for Research & Evaluation (AGREE)-II instrument and summarise the specific recommendations for neonatal hyperbilirubinemia in order to provide suggestions for future guideline development. Design: Systematic review. Interventions: We searched the PubMed, Embase, Medline and guideline databases for relevant articles on 10 April 2020. The studies were screened by two independent reviewers according to our inclusion criteria. Two reviewers independently extracted the descriptive data. Four appraisers assessed the guidelines using the AGREE-II instrument. Results: Our systematic review appraised 12 clinical practice guidelines for the diagnosis and management of neonatal hyperbilirubinemia. The 12 guidelines achieved an average score of 36%–89%. The guidelines received the highest scores for clarity of presentation and lowest scores for rigour of development. Most recommendations for diagnosis were relatively consistent, but recommendations regarding risk factors, the initiating threshold of treatment and pharmacotherapy varied. Conclusions: Our study revealed that current guidelines vary in the quality of the developing process and are inconsistent with regards to recommendations. Future guidelines should afford more attention to the quality of methodologies in guideline development, and more qualified evidence is needed to standardise the initiating threshold of treatment for neonatal hyperbilirubinemia.